Peningkatan Produktivitas Pertanian Melalui Penerapan Hidroponik dan Alat Penyiraman Berbasis Listrik Tenaga Surya di Desa Simbaringin, Mojokerto - Ahmadi; Jessica Putri Alwina; Asri Amalia (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
Sustainable Agriculture Innovation with Hydroponic Technology and Automatic Watering in Simbaringin Village Agriculture in Indonesia faces severe challenges, including land limitation and climate change. Innovations in agricultural methodologies, particularly through hydroponic technology and automatic watering systems that use solar power, have the potential to increase efficiency and productivity. The method used was observation and field research to determine the needs of the community. This research shows that the implementation of solar-powered automatic pumping systems is effective for improving access to clean water in agriculture, with ecological benefits as well as lower costs. In addition, hydroponics allows the cultivation of vegetables in a small space with sufficient nutrients, significantly increasing the speed and quality of plant growth. The results of the activity show that the increase in agricultural productivity through the application of hydroponics and solar electricity-based watering devices reflects the synergy between the implementing party and the villagers.